Bleb-related endophthalmitis - Angelito Braulio F. de Venecia III, MD; Ruben Lim Bon Siong,MD; Margarita Lat-Luna, MD (Philippine Journal of Ophthalmology)
Objective: To report the risk factors, diagnosis, and treatment of bleb-related infections.